UMP and BJTU Strategic Collaboration in dual degree programmes - Mimi Rabita, Abdul Wahit
PUTRAJAYA, 28 April 2021 – Universiti Malaysia Pahang (UMP) and Beijing Jiatong University (BJTU) China signed a memorandum of agreement (MoA) for collaboration in the UMP-BJTU Dual Degree Programmes.